2019
DOI: 10.3390/nu11081944
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor, Inhibition of Metastasis and Radiosensitizing Effects of Total Nutrition Formula on Lewis Tumor-Bearing Mice

Abstract: Non-small-cell lung cancer (NSCLC) causes high mortality. Radiotherapy is an induction regimen generally applied to patients with NSCLC. In view of therapeutic efficacy, the outcome is not appealing in addition to bringing about unwanted side effects. Total nutrition is a new trend in cancer therapy, which benefits cancer patients under radiotherapy. Male C57BL/6JNarl mice were experimentally divided into five groups: one control group, one T group (borne with Lewis lung carcinoma but no treatment), and three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…However, attenuation of muscle tissue loss was only observed for the suprahyoid muscles in the neck but not for gastrocnemius or soleus muscles in the lower leg ( 141 ). More recently, the effect of total nutrition formula on LLC-bearing mice was investigated ( 142 ). Total nutritional formula is an energy- and protein-dense oral nutritional supplement fortified with micronutrients such as vitamin D, vitamin A, coenzyme Q10 and selenium.…”
Section: Multinutrient Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, attenuation of muscle tissue loss was only observed for the suprahyoid muscles in the neck but not for gastrocnemius or soleus muscles in the lower leg ( 141 ). More recently, the effect of total nutrition formula on LLC-bearing mice was investigated ( 142 ). Total nutritional formula is an energy- and protein-dense oral nutritional supplement fortified with micronutrients such as vitamin D, vitamin A, coenzyme Q10 and selenium.…”
Section: Multinutrient Interventionsmentioning
confidence: 99%
“…Daily oral supplementation with total nutritional formula significantly suppressed tumor growth, while body weight loss and gastrocnemius muscle mass loss were significantly attenuated. Furthermore, the plasma levels of TNF-α and IL-6 were significantly decreased in LLC-bearing mice supplemented with total nutritional formula ( 142 ).…”
Section: Multinutrient Interventionsmentioning
confidence: 99%
“…Although we found that TNuF can downregulate tumoral expressions of caspase 3, Bcl-2, EGFR, VEGF, and HIF-α in our previous research [ 11 ], its effect on other pro-tumoral markers, such as STAT3, Ki-67, and AXL, was not evaluated. STAT3 is closely related to the cell proliferation induced by EGFR activation [ 25 ].…”
Section: Discussionmentioning
confidence: 70%
“…The hyperactivation of the angiogenic pathway in tumor cells can trigger a regeneration of tumoral vessels during fractional irradiation, resulting in the failure of RT [ 16 ]. In our previous study, the single treatment of TNuF was shown to downregulate the angiogenic pathway in LLC tumor cells [ 11 ]. Therefore, we detected the expression of hypoxia-inducible factor 1α (HIF-1α), tyrosine-protein kinase receptor UFO (AXL) mRNA, and vascular endothelial growth factor (VEGF) mRNA to observe the effect of TNuF on the angiogenic pathway in tumor cells ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation